Sustainable Development and Financial Markets: Old Paths and New Avenues. (March 2016) - Busch, Timo; Bauer, Rob; Orlitzky, Marc
This article explores the role of financial markets for sustainable development. More specifically, the authors ask to what extent financial markets foster and facilitate more sustainable business practices. The authors highlight that their current role is rather modest and conclude that, on the old paths, a paradoxical situation exists. On one hand, financial market participants increasingly integrate environmental, social, and governance (ESG) criteria into their investment decisions, whereas on the other hand, in terms of organizational reality, there seems to be no real shift toward more sustainable business practices. The authors identify two main challenges within the field of sustainable investments that are relevant for entering new avenues that may help overcome this situation. First, a reorientation toward a long-term paradigm for sustainable investments is important. Second, ESG data must become more trustworthy. From a theoretical point of view, the authors finally highlight the potential market consequences when ESG investment criteria are used.